Two Novel Sets of Genes Essential for Nicotine Degradation by Sphingomonas melonis TY - Wang, Haixia; Xie, Cuixiao; Zhu, Panpan; Zhou, Ning-Yi; Lu, Zhenmei (Frontiers in Microbiology, 2017)
Nicotine is a type of environmental pollutant present in the tobacco waste that is generated during tobacco manufacturing. Sphingomonas melonis TY can utilize nicotine as a sole source of carbon, nitrogen and energy via a variant of the pyridine and pyrrolidine pathway (the VPP pathway). In this study, we report the identification of two novel sets of genes, ndrA1A2A3 and ndrB1B2B3B4, which are crucial for nicotine degradation by strain TY. ndrA1A2A3 and ndrB1B2B3B4 exhibit similarity with both nicotine dehydrogenase ndh from Arthrobacter nicotinovorans and nicotine hydroxylase vppA from Ochrobactrum sp. SJY1. The transcriptional levels of ndrA1A2A3 and ndrB1B2B3B4 in strain TY were significantly upregulated in the presence of nicotine. Furthermore, ndrA1 or ndrB2 knockout resulted in a loss of the ability to degrade nicotine, whereas gene complementation restored the capacity of each mutant to utilize nicotine for growth. Biodegradation assays indicated that the mutant strains retained the ability to degrade the first intermediate in the pathway, 6-hydroxynicotine (6HN). However, heterologous expression of ndrA1A2A3 and ndrB1B2B3B4 did not confer nicotine dehydrogenase activity to E. coli DH5, Pseudomonas putida KT2440 or Sphingomonas aquatilis. These results provide information on the VPP pathway of nicotine degradation in Sphingomonas melonis TY, and we conclude that these two sets of genes have essential functions in the conversion of nicotine to 6HN in strain TY.